The PENGEMBANGAN MODUL PEMBELAJARAN SISTEM TRANSMISI OTOMATIS DI SMK KANISIUS 1 PAKEM - Irawan, Leonardus Adam; Rabiman, Rabiman; Alghozali, Muhammad Rafiq (Jurnal Taman Vokasi, 2024)
Abstract: The teacher-centered approach in the learning process leads to students' difficulties in independent learning. Modules serve as sources and learning materials that can be utilized by students for self-study. This research aims to: 1) Develop a learning module on automatic transmission in the automotive chassis system subject; 2) Validate the learning module with the expertise of subject matter and media specialists. This research, conducted as Research and Development (R&D), follows the ADDIE development model, consisting of the stages of analysis, design, development, implementation, and evaluation. The product developed from this research is a learning module. The research subjects are 11th-grade students from Kanisius 1 Pakem Vocational High School majoring in Light Vehicle Engineering. Validation of the learning module is carried out by subject matter experts and media specialists using a questionnaire. Data analysis employs a quantitative descriptive method. The research results indicate that: 1) The learning module on automatic transmission has been successfully created; 2) The module is deemed valid by subject matter experts with a validity rate of 93.3% and by media specialists with a validity rate of 94.4%; 3) Student responses show that this learning module is suitable for use in the educational process, with an overall suitability rate of 76.57%. Keywords: Development, Learning Module, Automatic Transmission, Automotive Chassis